The proteomic landscape of small urinary extracellular vesicles during kidney transplantation. Issue 1 (19th November 2020) - Braun, Fabian; Rinschen, Markus; Buchner, Denise; Bohl, Katrin; Plagmann, Ingo; Bachurski, Daniel; Richard Späth, Martin; Antczak, Philipp; Göbel, Heike; Klein, Corinna; Lackmann, Jan‐Wilm; Kretz, Oliver; et al.
Abstract: Kidney transplantation is the preferred renal replacement therapy available. Yet, long‐term transplant survival is unsatisfactory, partially due to insufficient possibilities of longitudinal monitoring and understanding of the biological processes after transplantation. Small urinary extracellular vesicles (suEVs) – as a non‐invasive source of information – were collected from 22 living donors and recipients. Unbiased proteomic analysis revealed temporal patterns of suEV protein signature and cellular processes involved in both early response and longer‐term graft adaptation. Complement activation was among the most dynamically regulated components. This unique atlas of the suEV proteome is provided through an online repository allowing dynamic interrogation by the user. Additionally, a correlative analysis identified putative prognostic markers of future allograft function. One of these markers – phosphoenol pyruvate carboxykinase (PCK2) – could be confirmed using targeted MS in an independent validation cohort of 22 additional patients. This study sheds light on the impact of kidney transplantation on urinary extracellular vesicle content and allows the first deduction of early molecular processes in transplant biology. Beyond that our data highlight the potential of suEVs as a source of biomarkers in this setting.